The influence of YouTube advertising on the attitude towards fruits and vegetable consumption among university students in Malaysia - Nur Shahafiqah Nadiah Jaffery; Sharifah Nurafizah Syed Annuar; Joseph Alagiaraj Thamburaj (Penerbit Universiti Kebangsaan Malaysia, 2020)
In 2005 with an emphasis on user-generated content, YouTube has become the predominant stage for online video around the world. Nowadays, YouTube has become increasingly attractive to advertisers, not only in conventional commercials but also in terms of promoting health marketing campaigns. This paper aims to investigate the influence that YouTube advertising has on attitudes towards fruits and vegetable consumption among university students, specifically in Malaysia. For this paper, Tripartite Attitude Model is employed as a foundation model to develop the conceptual framework. Perceived credibility, perceived usefulness, perceived video characteristics, number of likes, views, comments and replies are used as independent variables while attitudes towards fruits and vegetable consumption are treated as a dependent variable. A total of 280 offline questionnaires were distributed in eight local universities in Malaysia. The findings demonstrate that perceived usefulness and number of likes, views, comments and replies are the strongest positive drivers of attitudes towards fruits and vegetable consumption among university students in Malaysia. This paper provides novelty as it contributes to the marketing literature particularly in health marketing and social media studies. In addition, relevant local authorities and health marketers can also benefit from the findings in designing their future health communication campaign.